2015
DOI: 10.1007/s00268-015-3052-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Re‐recurrence After First Reoperative Surgery for Locoregional Recurrent/Persistent Papillary Thyroid Carcinoma

Abstract: Postoperative thyroglobulin after reoperative surgery predicted re-recurrence. Careful follow-up of these patients after reoperation is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 43 publications
1
35
1
2
Order By: Relevance
“…[2729] Now, it is known that ETE is divided into 2 grades: mETE and maximal ETE. Some researchers have reported that maximal ETE decreased the DFS of patients with PTC, while mETE has no impact on it.…”
Section: Discussionmentioning
confidence: 99%
“…[2729] Now, it is known that ETE is divided into 2 grades: mETE and maximal ETE. Some researchers have reported that maximal ETE decreased the DFS of patients with PTC, while mETE has no impact on it.…”
Section: Discussionmentioning
confidence: 99%
“…As is shown in Table , no obvious difference was observed in the temporary RLN paralysis rates (12.2% vs 7.0%; p = .658) and the permanent RLN paralysis rates (4.9% vs 2.3%; p = .966) between the 2 groups. Moreover, RLN function was sometimes difficult to be saved during reoperations because of invasion by tumors or metastatic lymph nodes . In fact, what we were eager to know was whether or not intermittent IONM could reduce the incidence of RLN paralysis caused by surgeon‐related factors and scar‐related factors, but not tumor‐related factors in which the condition of RLN injuries were inevitable.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas bilateral RLN damage may cause not only voice changes but also inspiratory dyspnea, and patients in such condition may need a tracheostomy . The incidence of permanent RLN paralysis and transient RLN paralysis is 4.1% and 9.5% after thyroid reoperation, respectively …”
Section: Introductionmentioning
confidence: 99%
“…Multifocality and higher thyroglobulin >20 ng/ml levels are defined risk factors for detection of malignancy in the residual tissue [10,11]. That residual disease is a major prognostic factor and total thyroidectomy decreases the risk of local recurrence and lymph-node metastasis [12,13], even in low-risk carcinoma [14,15] and anaplastic transformation of residual disease is always a possibility [3]. …”
Section: Discussionmentioning
confidence: 99%